The Many Flavors of Model‐Based Meta‐Analysis: Part I—Introduction and Landmark Data - M Boucher; M Bennetts (CPT: Pharmacometrics & Systems Pharmacology)
Meta‐analysis is an increasingly important aspect of drug development as companies look to benchmark their own compounds with the competition. There is scope to carry out a wide range of analyses addressing key research questions from preclinical through to postregistration. This set of tutorials will take the reader through key model‐based meta‐analysis (MBMA) methods with this first installment providing a general introduction before concentrating on classical and Bayesian methods for landmark data.